Analisis Manajemen Keuangan Syariah Di Masa Pandemi Covid-19 (Studi Pada Es Bulian) - Melnik Purnama Sari Nengsi; Mellya Embun Baining; Miftah Miftah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This proposal is backgrounded by the importance of implementing Islamic Financial Management for MSMEs in order to manage their money or assets in accordance with Islamic Law. At the time of the development of MSMEs in Indonesia, it was tested by the emergence of the Covid-19 outbreak in the midst of Indonesian society. The Covid-19 pandemic has also had an impact on MSMEs. This research method is a qualitative approach that aims to explore aka build a proposal aka meaning contained in a reality that occurs in the field. The respondent selection technique uses a type of Purposive Sampling technique that is produced through an interview process run by the author and a number of speakers selected by the researcher. The results showed that MSMEs have problems in their operations, especially in Islamic Financial Management. Based on the interview results, the factors inhibiting the implementation of Islamic financial management can be seen from the absence of financial statements and the limited knowledge of business owners on the technology that is developing now. MSMEs should be able to develop themselves by managing management finances in sharia, from the process of obtaining funds, using funds that should be planned so that they can be useful for the future and also the process of managing assets that should have special funds for their operation so that tetatp is maintained and can be durable for the future.